Acanthamoebakeratitis: improving the Scottish diagnostic service for the rapid molecular detection ofAcanthamoebaspecies. Issue 7 (July 2015) - Alexander, Claire Low; Coyne, Michael; Jones, Brian; Anijeet, Deepa
Abstract : N/A: Acanthamoeba species are responsible for causing the potentially sight‐threatening condition, Acanthamoeba keratitis, which is commonly associated with contact lens use. In this report, we highlight the challenges faced using conventional laboratory identification methods to identify this often under‐reported pathogen, and discuss the reasons for introducing the first national service in Scotland for the rapid and sensitive molecular identification of Acanthamoeba species. By comparing culture and molecular testing data from a total of 63 patients ( n = 80 samples) throughout Scotland presenting with ocular eye disease, we describe the improvement in detection rates where an additional four positive cases were identified using a molecular assay versus culture. The testing of a further ten patients by confocal imaging is also presented. This report emphasizes the importance of continuing to improve clinical laboratory services to ensure a prompt, correct diagnosis and better prognosis, in addition to raising awareness of this potentially debilitating opportunistic pathogen.